THE RELATIONSHIP OF STRATEGIC FORESIGHT IN ACHIEVING FINANCIAL SUSTAINABILITY: AN APPLIED STUDY IN A SAMPLE OF IRAQI PRIVATE COMMERCIAL BANKS - Ali Haitham Sufar; Dr. Aradin Hatem Khudair (Scholar Express Journals, 2022)
The research aims to determine the relationship of strategic foresight with its dimensions (environmental survey, information processing methods, networks and individuals, organization and culture) in financial sustainability with its dimensions (cash and its equivalents, credit, revenues) and the degree of arrangement of these dimensions according to their importance and priority, as well as revealing The moral differences in the respondents’ response to the questionnaire’s paragraphs according to the surveyed banks. The study problem was identified through several questions that centered on whether there is a relationship for strategic foresight in achieving financial sustainability for the banks investigated, 157 people who are at the administrative levels (high, middle, and executive) in the Iraqi private commercial banks (the National Bank of Iraq, Ashur Bank, Gulf Commercial Bank, Trans-Iraq Investment Bank) and the financial statements and reports of those banks for the years (2014 - 2019) were also relied upon in interpreting the results as well as conducting personal interviews with some officials in the surveyed banks, the data were analyzed on statistical programs (MICROSOFT EXCEL), (SPSS V.26) in calculating (arithmetic mean, standard deviation, relative importance, simple regression coefficient, Pearson correlation coefficient, path analysis)
Keywords: Strategic Foresight; Financial Sustainability; importance; coefficient